Desensitisasi Cepat Sebagai Prosedur Induksi Toleransi Terhadap Alergen - Basudewa, I Made; Suardamana, Ketut (Green Publisher Indonesia, 2025)
Immediate hypersensitivity reactions are one of the leading causes of morbidity in the world. Immediate hypersensitivity reactions occur immediately following exposure to the antigen. This reaction can manifest as mild, such as itching, or severe, such as bronchospasm, shock, and death. Immediate hypersensitivity reactions are included in type 1 hypersensitivity reactions which are mediated by immunoglobulin E. In some cases, there are conditions where a patient must consume a known allergen, which is usually in the form of a drug due to an illness. This condition often occurs in patients with infections for whom there are no other antibiotic options or in patients with cardiovascular disorders who must take aspirin. Rapid desensitization is a modality that can be used to treat this condition. This procedure aims to induce tolerance to a known allergen. This procedure has several stages and must be carried out with close monitoring. The end result of this procedure is the induction of tolerance to allergens, so that these allergens can be safely used by patients. Several protocols have been issued to perform rapid desensitization. Existing protocols for rapid desensitization include rapid desensitization protocols to penicillin, co-trimoxazole and aspirin.